Genome‐based comparison between the recombinant SARS‐CoV‐2 XBB and its parental lineages. Issue 3 (9th March 2023) - Scarpa, Fabio; Sanna, Daria; Azzena, Ilenia; Casu, Marco; Cossu, Piero; Fiori, Pier Luigi; Benvenuto, Domenico; Imperia, Elena; Giovanetti, Marta; Ceccarelli, Giancarlo; Cauda, Roberto; Cassone, Antonio; et al.
Abstract: Recombination is the main contributor to RNA virus evolution, and SARS‐CoV‐2 during the pandemic produced several recombinants. The most recent SARS‐CoV‐2 recombinant is the lineage labeled XBB, also known as Gryphon, which arose from BJ.1 and BM.1.1.1. Here we performed a genome‐based survey aimed to compare the new recombinant with its parental lineages that never became dominant. Genetic analyses indicated that the recombinant XBB and its first descendant XBB.1 show an evolutionary condition typical of an evolutionary blind background with no further epidemiologically relevant descendant. Genetic variability and expansion capabilities are slightly higher than parental lineages. Bayesian Skyline Plot indicates that XBB reached its plateau around October 6, 2022 and after an initial rapid growth the viral population size did not further expand, and around November 10, 2022 its levels of genetic variability decreased. Simultaneously with the reduction of the XBB population size, an increase of the genetic variability of its first sub‐lineage XBB.1 occurred, that in turn reached the plateau around November 9, 2022 showing a kind of vicariance with its direct progenitors. Structure analysis indicates that the affinity for ACE2 surface in XBB/XBB.1 RBDs is weaker than for BA.2 RBD. In conclusion, at present XBB and XBB.1 do not show evidence about a particular danger or high expansion capability. Genome‐based monitoring must continue uninterrupted to individuate if further mutations can make XBB more dangerous or generate new subvariants with different expansion capability.